Pemanfaatan Kecerdasan Artifisial (AI) untuk Perancangan Pembelajaran dan Pembuatan Media Ajar Inovatif bagi Guru - Adhitya, Wisnu Rayhan; Adhitya, Tiara Reizsa; Dody Hidayat (Prioritas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Digital transformation in the world of education requires teachers to adopt innovative technologies to improve the quality of learning. Generative Artificial Intelligence (AI) offers great potential to help teachers design learning and create more optimal and creative teaching media. However, teachers' understanding and skills in utilizing Generative AI tools are often still limited. This community service activity aims to improve the conceptual understanding and practical skills of teachers at the Ar-Rahman Medan Education Foundation in utilizing Generative AI to optimize learning design and create innovative teaching media. The implementation method of the activity includes an initial survey, a 2-day intensive workshop that includes material presentation, demonstration of AI tools (such as ChatGPT, Canva AI, Pictory AI), guided practice sessions (hands-on), discussions, and post-workshop assistance. Evaluation was carried out through pre-test, post-test, observation, product analysis, and satisfaction questionnaires. The results of the activity showed a significant increase in participants' conceptual understanding of Generative AI, as evidenced by an increase in the average post-test score of 0.00 compared to the pre-test. Participants also showed an increase in practical skills in using various AI tools to design learning components and produce innovative teaching media. The level of participant satisfaction with the implementation of the workshop was very high, with an average score. It was concluded that the training on the use of Generative AI was effective in improving teacher competence and answering the need for learning innovation in the digital era. It is recommended that there be a tiered training program and institutional support for the sustainability of implementation. Keywords: Generative Artificial Intelligence, Teacher Training, Learning Media, Educational Innovation, Learning Design